STUDI LINGUISTIK ANTROPOLOGI WACANA RITUAL PEMELIHARAAN PADI PADA MASYARAKAT PETANI DI BALI - I Gde Wayan Soken Bandana (Balai Bahasa Sulawesi Selatan, 2011)
Rice cultivation ritual discourse is a Balinese discourse that is related to ritual of rice plant cultivation, which isuntil at present time still carried out by farmers in Bali. The ritual is performed since the rice age of twelve daystill the harvest time arrives. The study analyzes ritual discourse, ritual shape as a form of offerings, and themeaning of the ritual. In the end of the study, it is concluded that each of ritual discourse has ritual form anddifferent meaning. In general, ritual is aimed at Dewi Sri as manifestation of God. In this respect, rice plant isalso identical with Dewi Sri's character. AbstrakWacana ritual pemeliharaan padi adalah sebuah wacana bahasa Bali yang berkaitan denganritual pemeliharaan tanaman padi yang sampai saat ini masih tetap dilaksanakan oleh parapetani di Bali. Ritual tersebut dilaksanakan sejak padi berumur duabelas hari sampai saatnyamusim panen tiba. Dalam tulisan ini dibahas wacana ritual, wujud ritual sebagai bentukpersembahan, dan makna yang terkandung di baliknya. Pada akhir tulisan ini disimpulkanbahwa setiap wacana ritual itu memiliki wujud ritual dan makna yang berbeda-beda. Secaraumum, ritual ditujukan kepada manifestasi Tuhan sebagai Dewi Sri. Dalam hal ini tanamanpadi juga diidentikkan sebagai sosok Dewi Sri.